Computer numerical control machines and computer aided manufacture - Radhakrishnan, P. (Pezhingattil), 1944- (New Academic Science, 2015)
"Knowledge of computer programming and electronics is a presumption. Primary focus is laid on CNC machine tools. Training requirements of technicians and engineers in tools manufacturing are highlighted. Use of robots in computer aided manufacture are illustrated. The book attempts a detailed coverage of CNC machine tools. CNC systems, constructional features, process planning and programming have been dealt with in detail. Knowledge of CNC programming using software packages, programmable machine control and computer aided inspection are essential for the effective operation of CNC machines. Chapters on economics of manufacturing effective utilization and maintenance will be useful for shop floor personnel. The chapter on manufacturing automation is included to introduce concepts of increasing productivity with CNC machines. A few chapters on robotics have been included in the book to introduce the reader to the use of robotics in computer aided manufacture."--Amazon.in